The tissue and circulating cell‐free DNA‐derived genetic landscape of premalignant colorectal lesions and its application for early diagnosis of colorectal cancer - Qingjian Chen; Yu‐Hong Xu; Shiyang Kang; WuHao Lin; Linna Luo; Luping Yang; Qi‐Hua Zhang; Pan Yang; Jia‐Qian Huang; Xiaoni Zhang; Jing Zhang; Qi Zhao; et al. (MedComm)
Abstract Colorectal adenomas (CRAs) represent precancerous lesions that precede the development of colorectal cancer (CRC). Regular monitoring of CRAs can hinder the progression into carcinoma. To explore the utility of tissue DNA and circulating cell‐free DNA (cfDNA) in early diagnosis of CRC, we retrospectively sequenced paired tissue and plasma samples from 85 patients with conventional CRAs. The genetic alterations identified were compared with those from 78 stage‐I CRC patients (CRC‐I) in the ChangKang project. Within the CRA cohort, we pinpointed 12 genes, notably APC, KRAS, and SOX9, that exhibited significant mutated rates in tissue. Patients harboring KMT2C and KMT2D mutations displayed persistent polyps. By comparing with the mutational profiles of metastatic CRC plasma samples, we found that ZNF717 was exclusively mutated in CRAs, while KMT2C and KMT2D mutations were detected in both CRA and CRC. The presence of cfDNA mutations in plasma was validated through polymerase chain reaction, enhancing the feasibility of using cfDNA mutations for early CRC screening. Compared with CRC‐I, CRAs exhibited a reduced frequency of TP53 and PIK3CA somatic mutations and underwent non‐neutral evolution more often. We established a random forest model based on 15 characteristic genes to distinguish CRA and CRC, achieving an area under the curve of 0.89. Through this endeavor, we identified two novel genes, CNTNAP5 and GATA6, implicated in CRC carcinogenesis. Overall, our findings reveal convincing biomarkers markers for detecting CRAs with a propensity for CRC development, highlighting the importance of early genetic screening in CRC prevention.